Image-making and Architecture: A Digital Medium for Qualitative Design Representative - Dewa Ayu Ketut Septika (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2020)
Architecture is inseparable from visual aspects in the form of representation as a way to establish communication. Due to digitalization and the rapid development of technology, there has been a shift in the paradigm of image representation. Manual images become digital images, from sketching and drawing to image-making and rendering. Digital rendering is considered to be object-oriented and quantitative. It has the characteristics of being precise, fast, reflecting form and materiality, with a photorealistic image as a result. There is no visible involvement of subjects such as architects, image-maker, and observers in the process because the image represents the final outcome. Here, the role of representation to evoke imagination and deeper interpretation is lost, because it does not leave room for intervention and contemplation of the design. That is why another kind of digital method emerged in the world of representation, instead of “rendering” the design as an image, it is relevant to the act of “making” an image as design representation. Its characteristic as a representation method makes the produced images have the ability to be evocative, in order to make its viewers contemplate and interpret the design, which makes it a qualitative representation. The aim of this paper is to understand the act of image-making through digital collage as a medium for qualitative representation in architectural design. By comparing digital rendering and collage images obtained through literature studies, this paper wants to offer the author’s viewpoint on the qualities and experiences brought by architectural representation.